The Role of Traditional Institutions in Resolving Bali's Customary Criminal Law Using a Restorative Justice Approach - sinergilp, Zufarnesia; Muhammad Arif Sahlepi; Ismaidar (International Journal of Synergy in Law, Criminal, and Justice, 2024)
The Balinese legal system, deeply rooted in customary law, emphasizes reconciliation and the restoration of community harmony over punitive measures. Institutions such as Desa Adat and Majelis Desa Pekraman are central to implementing these restorative principles, serving not only as mediators in disputes but also as custodians of cultural values. This study examines how these institutions operate, their effectiveness in resolving conflicts, and their contribution to maintaining social equilibrium within Balinese society. Using qualitative methodologies, including interviews with local leaders and case studies of traditional conflict resolution processes, the research highlights the success of these institutions in addressing the root causes of disputes and fostering communal cohesion. The findings underscore the importance of integrating traditional practices with modern legal frameworks to enhance justice systems worldwide. By bridging the gap between customary law and contemporary legal practices, this paper offers insights into the potential for a more harmonious coexistence between different justice paradigms, emphasizing the role of culturally sensitive legal solutions in a globalized world.